2022
DOI: 10.1111/jch.14623
|View full text |Cite
|
Sign up to set email alerts
|

Sustained cannabis use does not predispose clinical hypertension: Findings from a national survey

Abstract: Cannabis is among the most used recreational and medicinal drugs in the United States.The effects of chronic use on hypertension remain poorly understood. Our study retrospectively evaluated data collected by the National Health and Nutrition Examination Survey from 2017 to 2018. Cannabis use was measured with five metrics: (1) sustained use at any point in the past, (2) sustained use within the past year, (3) frequency of use, (4) age of first cannabis use, and (5) current use. Hypertension status was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…Although some studies found associations between chronic diseases, for example, hypertension and diabetes mellitus, and risk of or worsening depression, 27,28 our data did not show any significant associations between presence of chronic diseases and worsening depression risk. Our relatively small sample size might be partly accountable for that.…”
Section: Discussioncontrasting
confidence: 98%
“…Although some studies found associations between chronic diseases, for example, hypertension and diabetes mellitus, and risk of or worsening depression, 27,28 our data did not show any significant associations between presence of chronic diseases and worsening depression risk. Our relatively small sample size might be partly accountable for that.…”
Section: Discussioncontrasting
confidence: 98%
“…For diagnosing dengue fever the Platelets indices were used as predictive markers because they show sensitivity to dengue fever. Due to decreased production of platelets in the bone marrow or increased destruction and clearance of platelets from peripheral blood were considered as the main cause of low platelet count in Dengue patients 36 .…”
Section: Discussionmentioning
confidence: 99%